Cognitive impairment restoration in patients suffered with stroke during the post-COVID period - Stoyanov, O.; Son, A.; Vastyanov, R.; Turchin, N.; Gruzevsky, O.; Yermuraki, P.; Dzygal, O.; Vastyanov, M. (Journal of Education, Health and Sport, 2022)
Frequency of vascular complications, including strokes, in patients suffered from COVID-19 infection is known to be increased up to 8 times, especially compared with influenza. The purpose: to investigate the fundamental mechanisms of brain ischemia in the patients with mnestic dysfunctions who previously underwent COVID-19 through pharmacocorrection via Phenibut (g-amino-b-phenylbutyric acid hydrochloride) and magnetic therapy in the early recovery period of ischemic stroke. The authors describe the possibilities of cognitive rehabilitation for people who have had ischemic stroke in the post-COVID period. Considering that the presence of mnestic dysfunctions has a negative impact on the process of rehabilitation of cerebral accidents, the fundamental mechanisms of brain ischemia in patients with mnestic dysfunctions in the early recovery period in patients who have undergone COVID-19 have been studied through pharmacocorrection via Phenibut (g-amino-b-phenylbutyric acid hydrochloride) and magnetic therapy. 46 patients aged 40 to 60 years were examined. A comparative study of three randomized clinical groups of patients with separate and complex use of Phenibut and magnetic stimulation. The effectiveness of the proposed therapy in restoring executive functions was established on the basis of indicators of the MMSE scale, the test for the study of frontal dysfunction – FAB, regression of depressive symptoms and is characterized by a decrease in the score on the GDS scale. The authors conclude that mnestic disorders are a functional "target" in cerebral ischemia in the post-COVID period, which requires close attention in relation to pharmacocorrection methods and comprehensive rehabilitation and further research, including the elucidate the pathogenetic mechanisms of cerebral ischemia.